PENGARUH MUTASI PEGAWAI TERHADAP MOTIVASI KERJA APARATUR SIPIL NEGARA DI KANTOR BADAN KEPEGAWAIAN DAERAH (BKD) KABUPATEN NIAS BARAT - Darma Manalu (LPPM Universitas HKBP Nommensen, 2021)
The State Civil Apparatus (ASN), which is the State Apparatus that organizes the government in carrying out national development, is the backbone of the government. The smooth running of government and the implementation of national development depends on the perfection of the state apparatus both at the central and regional levels. In order to achieve the national goals as stated above, it is necessary to have a State Civil Apparatus who is full ofwillingness and obedience to Pancasila, the 1945 Constitution, the State and the Government and is united, has good mentality, is authoritative, strong, efficient, clean, of high quality and aware of their responsibilities as elements of the State Apparatus, State servants and public servants. To realize the perfect State Civil Apparatus as intended above, the Civil Apparatus needs to be fostered as well as possible. One form of fostering the State Civil Apparatus is Mutation as an incarnation or embodiment of organizational dynamics which is used as a way to achieve organizational goals. In the implementation of mutations, it must be based on an objective assessment considering that the transfer system is intended to provide opportunities for State Civil Apparatus to develop their potential. The work motivation of the State Civil Apparatus can also decrease if the superiors do not pay attention to the interests of their subordinates. This will reduce the work motivation of both the State Civil Apparatus. Indicators of declining morale include: low productivity, high employee absenteeism, and others. Thus, it will certainly affect the work motivation of employees in an organization. Mutation will have a positive impact on employees, such as increasing work morale. However, if the mutation is carried out without paying close attention and without being based on convincing arguments, the mutation will have a negative impact on the employee and the organization.